Transcranial Direct Current Stimulation (TDCS). - Yusra Saleem; Komal .; Riaz , Stephen (International Journal of Endorsing Health Science Research, 2022)
Transcranial direct current stimulation (TDCS) is a neuromodulatory device that is used for its ability to enhance cognitive and behavioral performance. Human studies suggest that TDCS modulates cortical excitability during stimulation by nonsynaptic changes of the cells, along with evidence that the after-effects of TDCS are driven by synaptic modification. TDCS represents a potential intervention to enhance cognition across clinical populations, including mild cognitive impairment among psychological and neurological disorders. Studies suggest that TDCS might be helpful in treating depression with appropriate current, size of electrodes, and employment of montages. TDCS opens a new perspective in treating major depressive disorder (MDD) because of its ability to modulate cortical excitability and induce long-lasting effects.